Correlation of the Ki67 Working Group prognostic risk categories with the Oncotype DX Recurrence Score in early breast cancer. Issue 20 (10th August 2022) - Patel, Rima; Hovstadius, Malin; Kier, Melanie W.; Moshier, Erin L.; Zimmerman, Brittney S.; Cascetta, Krystal; Jaffer, Shabnam; Sparano, Joseph A.; Tiersten, Amy
Abstract : Background: The relationship between Ki67 assessed by immunohistochemistry (IHC) and the Oncotype DX Recurrence Score (RS) is unclear. The objective of this study was to determine the correlation between the 21‐gene RS and IHC‐measured Ki67 with the prognostic classification groups recommended by the International Ki67 Working Group (IKWG). Methods: The authors performed a retrospective chart review of women who had hormone receptor (HR)–positive, human epidermal growth factor receptor 2–negative early breast cancer with zero to three positive lymph nodes and both Ki67 and the 21‐gene RS performed at their institution from 2013 to 2021. Patients were categorized into low (≤5%), intermediate (6%–29%), and high Ki67 groups (≥30%) according to IKWG recommendations. Overall agreement and risk‐stratified agreement between Ki67 and RS were assessed with the proportion of agreement and the κ statistic. Results: The study included 525 patients with HR‐positive breast cancer. Among the 49% of patients with intermediate Ki67 values of 6%–29%, the distribution of low (0–10), intermediate (11–25), and high RS (26–100) was 19%, 66%, and 15%, respectively. There was slight agreement (κ = 0.01–0.20) between Ki67 and RS (κ = 0.027) in the overall population, although this was not significant ( p = .1985). There was fair agreement (κ = 0.21–0.40) between high Ki67 and RS values (κ = 0.280; p < .0001). A higher progesterone receptor percentage was associated with lower RS values ( p > .0001) but not lower Ki67 values. A positive nodal status and a larger tumor size were associated with higher Ki67 values ( p = .0059 and p < .0001) but not with RS. Conclusions: In this group of patients selected to have a 21‐gene RS, there was no significant correlation between Ki67 and RS in the overall population, and there was fair agreement between high Ki67 and high RS values. Lay summary: In patients with early‐stage, hormone receptor–positive breast cancer, decisions on adjuvant chemotherapy are based on certain biological features of the cancer and genomic assays such as the Oncotype DX Recurrence Score (RS). The goal of this study was to determine the correlation between Ki67, a marker of proliferation, and the Oncotype DX RS, a 21‐gene assay demonstrated to be predictive of an adjuvant chemotherapy benefit in patients with early‐stage breast cancer. In 525 patients, the authors did not find a significant correlation between Ki67 and RS. Abstract : In this retrospective study of 525 patients with early‐stage, hormone receptor–positive breast cancer, there was no significant correlation between immunohistochemistry‐measured Ki67 and the 21‐gene recurrence score in the overall population, and with the International Ki67 Working Group risk categories, only fair agreement was found between high Ki67 values and high recurrence scores.